MAI, UMP to produce more than 5,600 local automotive engineers in various dicipline by 2015 - UMP, PNC
The Malaysia Automotive Institute (MAI), an agency under the Ministry of International Trade & Industry (MITI) announced its strategic alliance with Universiti Malaysia Pahang (UMP), to produce engineers in various automotive disciplines which in-line with MAI directive in collaboration with Institution of Higher Learning in producing more than 5600 automotive engineers by 2015 on 15 March 2011.